THE LIKELY ECONOMIC CONSEQUENCES FROM RAISING NEW YORK'S CIGARETTE EXCISE TAX BY $0.25 PER PACK (Tufts Archival Research Center, 2007)
Philip Morris report on the likely economic consequences of raising New York's cigarette excise tax. Explores job, sales, and income losses and affects on other states. Accuses taxes of being unfair based on their regressivity and questions the stability of tobacco taxes. Includes charts with statistics supporting arguments.